2013
DOI: 10.1161/circulationaha.113.004840
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Diagnosis of Long QT Syndrome by Magnetocardiography

Abstract: Background The electrophysiology of long QT syndrome (LQTS) in utero is virtually unstudied. Our goal here was to evaluate the efficacy of fetal magnetocardiography (fMCG) for diagnosis and prognosis of fetuses at risk of LQTS. Methods and Results We reviewed the pre/postnatal medical records of 30 fetuses referred for fMCG due to a family history of LQTS (n=17); neonatal/childhood sudden cardiac death (n=3) and/or presentation of prenatal LQTS rhythms (n=12): 2° AVB, ventricular tachycardia, heart rate < 3r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 19 publications
1
94
0
Order By: Relevance
“…435 Management of the fetus with suspected LQTS includes close observation, postnatal evaluation, and measurement of the QTc by fMCG or fetal electrocardiography if available. 436 Fetal treatment is not recommended for bradycardia; however, torsades de pointes and ventricular tachycardia (VT) require treatment if they occur (Tables 13 and14). 435 Maternal electrolyte abnormalities, especially hypomagnesemia and hypocalcemia, should be avoided, as well as drugs and anesthetic agents that lengthen the QT interval.…”
Section: Lqts and Other Ion Channelopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…435 Management of the fetus with suspected LQTS includes close observation, postnatal evaluation, and measurement of the QTc by fMCG or fetal electrocardiography if available. 436 Fetal treatment is not recommended for bradycardia; however, torsades de pointes and ventricular tachycardia (VT) require treatment if they occur (Tables 13 and14). 435 Maternal electrolyte abnormalities, especially hypomagnesemia and hypocalcemia, should be avoided, as well as drugs and anesthetic agents that lengthen the QT interval.…”
Section: Lqts and Other Ion Channelopathiesmentioning
confidence: 99%
“…353 Unfortunately, although terbutaline may increase fetal rates and prolong pregnancy, no studies have shown survival benefit. Although there is merit to the notion, because of significant technical limitations, fetal pacing has not been shown to be successful in improving survival or prolonging gestation 436 and therefore at present is experimental and not recommended as part of usual care.…”
Section: Av Blockmentioning
confidence: 99%
“…Multichannel MCG has been used clinically for the detection and diagnosis of fetal arrhythmias, 20 and for analysis in healthy adults as well as detection of abnormalities in various heart diseases. 7,21-23 Korhonen et al have reported the usefulness of QRS fragmentation detected quantitatively using the time-waveforms of MCG for predicting MACE in patients with previous myocardial infarction.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…11 In addition to a low baseline heart rate, nonreactive heart rate patterns are also suggestive in LQTS fetuses and may be explained by lower-than-normal right sympathetic cardiac activity or a blunted response to a sympathetic drive, as seen postnatally. 8 LQTS with 2:1 AVB is commonly observed during the fetal and neonatal periods, 9,10 but rarely observed in childhood and adulthood. In neonates with LQT2 and LQT3, 2:1 AVB was observed in 55% and 83% of the patients, respectively (Figure 1).…”
mentioning
confidence: 99%
“…10 AVB may be caused by functional block of the ventricle, because of prolongation of the ventricular refractory period, and in the majority of patients the atrioventricular conduction returns with a significant decrease in the QTc interval during the follow-up period. 8 That may explain the rare occurrence of AVB in older children and adults with LQTS.…”
mentioning
confidence: 99%